Mixed solid electrolyte and preparation method and application thereof
By doping modified polyvinylidene fluoride-hexafluoropropylene copolymer with lithium titanium phosphate and lithium taurate for solid electrolyte, the problem of insufficient flexibility and conductivity in solid-state batteries is solved, and high-performance Hybrid solid electrolyte, suitable for lithium batteries, improves electrochemical stability and mechanical strength.
Patent Information
- Application Number
- CN202411052112.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-01-07
AI Technical Summary
The existing solid electrolytes have shortcomings in flexibility, interface contact and conductivity, resulting in energy density, electrochemical stability and safety problems of solid batteries, especially the poor flexibility of traditional inorganic solid electrolytes and the conductivity of polymer electrolytes. Low.
Polyvinylidene fluoride-hexafluoropropylene copolymer doped with inorganic solid electrolyte titanium aluminum phosphate and lithium taurate are used to form a mixture of high ionic conductivity, high mobility and heat resistance through recombination and modification. Solid electrolytes, enhancing electrochemical stability and mechanical strength.
Achieved high ionic conductivity, high migration number, long electrochemical stability window and high flexibility hybrid solid electrolyte, suitable for quasi-solid and all-solid lithium batteries, improve thermal stability and mechanical strength, reduce interface impedance, and solve the problem of The problem of insufficient flexibility and conductivity of traditional electrolytes.
Smart Images

Figure CN119275441A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a mixed solid electrolyte and a preparation method and application thereof. Background Art
[0002] With the rapid promotion of new energy vehicles, battery energy density, electrochemical stability and safety issues continue to receive attention. Compared with mainstream liquid lithium batteries, solid-state batteries have the advantages of higher energy density, stronger electrochemical stability and higher safety. Solid electrolyte is one of the most important parts of solid-state batteries, which plays an important role in ion transport. In theory, solid-state batteries can be smaller and lighter with the same energy density as liquid batteries, and are easy to use and have good thermal stability.
[0003] Current research on solid electrolytes is mainly focused on inorganic solid electrolytes and polymer electrolytes. Inorganic solid electrolytes have high ionic conductivity, but their material flexibility is poor, the interface contact with the electrode material is poor, and the ion transmission kinetics in the solid material are low, resulting in excessively high interface impedance. Polymer electrolytes have the characteristics of low density, easy processing, flexible manufacturing appearance, and high safety factor, but the ionic conductivity of polymer electrolytes is low. Although in the prior art, polymer electrolytes are often mixed with lithium salts to improve their conductivity, a large amount of additives are often used to increase the preparation cost, increase the preparation process, extend the preparation cycle, and reduce the preparation efficiency; at the same time, the supporting strength of the modified polymer electrolyte is poor. Summary of the invention
[0004] The purpose of the present invention is to provide a hybrid solid electrolyte and its preparation method and application, which is formed by mixing an inorganic solid electrolyte lithium aluminum titanium phosphate and a polyvinylidene fluoride-hexafluoropropylene copolymer doped and modified by lithium taurine, thereby obtaining a hybrid solid electrolyte with high ionic conductivity, high ion migration number, long electrochemical stability window, good heat resistance and high flexibility, which can be applied to quasi-solid-state and all-solid-state lithium batteries.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] In a first aspect, an embodiment of the present invention provides a mixed solid electrolyte composition, which is composed of lithium aluminum titanium phosphate and lithium taurate doped modified polyvinylidene fluoride-hexafluoropropylene copolymer, wherein the content of lithium aluminum titanium phosphate is 60%-70wt.%.
[0007] In some other embodiments, the lithium taurine doped modified polyvinylidene fluoride-hexafluoropropylene copolymer is a product obtained by adding lithium taurine, a catalyst, and polyvinylidene fluoride-hexafluoropropylene copolymer to a solvent, stirring and heating to 90-140° C., reacting for 5-20 hours, and then cooling.
[0008] In some other embodiments, the mass ratio of lithium taurate, catalyst, and polyvinylidene fluoride-hexafluoropropylene copolymer is (1.2-2.4): (0.2-0.239): (0.038-0.076); the catalyst is MgO or MnO2; the solvent is DMF;
[0009] Alternatively, the number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 200,000 to 500,000.
[0010] The hybrid solid electrolyte composition of the present invention is composed of an inorganic solid electrolyte lithium aluminum titanium phosphate and a polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium taurine, which can better fit the negative electrode and the air positive electrode, reduce the interface impedance, and thus directly improve the thermal stability and electrochemical performance of the solid-state battery. Among them, the polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium sulfonate provides support and wrapping for the lithium aluminum titanium phosphate, solving the problem of Ti in the traditional LiSICON inorganic solid electrolyte lithium aluminum titanium phosphate (LATP). 4+ To address the problem of attack on the active metal negative electrode of metal batteries, lithium aluminum titanium phosphate is filled in the polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium sulfonate, which increases the conductivity of the polymer electrolyte; improves the mechanical strength and stability under high temperature and high pressure environments, and avoids possible deformation, rupture, decomposition or failure.
[0011] In a second aspect, an embodiment of the present invention provides a hybrid solid electrolyte film, which is obtained by uniformly mixing the hybrid solid electrolyte composition described in the first aspect with a dispersant, coating it on a substrate, and drying it.
[0012] In some embodiments, the dispersant is N,N-dimethylformamide and acetone, and the volume ratio of N,N-dimethylformamide to acetone is 1:(2-3); the thickness of the hybrid solid electrolyte film is 100-130 μm.
[0013] In a third aspect, an embodiment of the present invention provides a method for preparing the hybrid solid electrolyte film described in the second aspect, wherein lithium aluminum titanium phosphate, lithium taurine doped modified polyvinylidene fluoride-hexafluoropropylene copolymer and a dispersant are uniformly mixed, coated on a substrate, and vacuum dried to obtain the film;
[0014] Or, the dispersant is N,N-dimethylformamide and acetone, and the volume ratio of N,N-dimethylformamide to acetone is 1:(2-3);
[0015] Alternatively, the particle size of the lithium aluminum titanium phosphate is 200 to 400 nm.
[0016] In some other embodiments, the preparation method of the lithium taurine is as follows: dissolving taurine and lithium hydroxide in deionized water at a molar ratio of (0.1 to 0.5):1; conducting a hydrothermal reaction at 60 to 80°C for 3 to 12 hours to obtain a reaction product; and freeze-drying the product at -30 to -40°C.
[0017] The lithium taurine prepared by hydrothermal reaction combined with freeze-drying in the present invention is sufficiently pure, and the lithium taurine containing crystal water caused by direct drying treatment is avoided.
[0018] In some other embodiments, the method for doping and modifying polyvinylidene fluoride-hexafluoropropylene copolymer with lithium taurine is to add lithium taurine, a catalyst, and polyvinylidene fluoride-hexafluoropropylene copolymer to a solvent, stir and heat to 90-140° C., react for 5-20 hours, and then cool to obtain a product;
[0019] Or, the mass ratio of lithium taurate, polyvinylidene fluoride-hexafluoropropylene and catalyst is (1.2-2.4): (0.2-0.239): (0.038-0.076);
[0020] Alternatively, the catalyst is MgO or MnO2.
[0021] The preparation method of the present application is relatively simple and the reaction conditions are relatively mild, and the raw materials are cheap and readily available. Among them, lithium taurine doped modified polyvinylidene fluoride-hexafluoropropylene copolymer is beneficial to improve the conductivity and lithium ion migration number of vinylidene fluoride-hexafluoropropylene copolymer at room temperature, and increase the electrochemical window.
[0022] In a fourth aspect, an embodiment of the present invention provides an application of the hybrid solid electrolyte film described in the second aspect in a lithium-air or lithium-oxygen battery.
[0023] In a fifth aspect, an embodiment of the present invention provides a lithium-air or lithium-oxygen battery, comprising an air positive electrode, the hybrid solid electrolyte film described in the second aspect, and a metallic lithium negative electrode;
[0024] Preferably, the air positive electrode comprises a positive electrode current collector, carbon paper, a conductive material, a binder and a catalyst;
[0025] Further preferably, the conductive material is conductive carbon black, carbon nanotubes, acetylene black, or ketjen carbon;
[0026] More preferably, the binder is polyvinylidene fluoride or polytetrafluoroethylene.
[0027] The beneficial effects of the above embodiments of the present invention are as follows:
[0028] (1) The present invention improves the conductivity and lithium ion migration number of the polyvinylidene fluoride-hexafluoropropylene copolymer at room temperature by doping with lithium taurine, and increases the electrochemical window height.
[0029] (2) The present invention combines an inorganic solid electrolyte lithium titanium aluminum phosphate with a lithium taurine-doped modified polyvinylidene fluoride-hexafluoropropylene copolymer (high-density lithium titanium aluminum phosphate is precipitated, and the upper polymer layer is stable, thereby obtaining a polymer layer) to obtain a hybrid solid electrolyte with high ionic conductivity, high ion migration number, long electrochemical stability window, good heat resistance and high flexibility, so that it can be used in quasi-solid-state and all-solid-state lithium batteries. The polymer thin layer is close to the lithium negative electrode to protect the active metal.
[0030] (3) The polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium sulfonate of the present invention provides support and wrapping for lithium aluminum titanium phosphate, solving the problem of Ti in the traditional LiSICON inorganic solid electrolyte lithium aluminum titanium phosphate (LATP). 4+ To address the problem of attack on the active metal negative electrode of metal batteries, lithium aluminum titanium phosphate is filled in the polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium sulfonate, which increases the conductivity of the polymer electrolyte; improves the mechanical strength and stability under high temperature and high pressure environments, and avoids possible deformation, rupture, decomposition or failure.
[0031] (4) The preparation method of the present application is simple and the preparation conditions are mild. The raw materials are cheap and easily available, which is conducive to promoting the industrialization and application of hybrid solid electrolytes in lithium-air or lithium-oxygen batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0033] Figure 1 is an optical photograph of the hybrid solid electrolyte prepared in Example 1 of the present invention;
[0034] Figure 2 Scanning electron microscope images of Examples 1 to 3 of the present invention and Comparative Example 1, wherein Example 1 is HSE-SO3-1, Example 2 is HSE-SO3-2, Example 3 is HSE-SO3-3, and Comparative Example 1 is HSE-SO3-0;
[0035] Figure 3(a) X-ray diffraction patterns of the mixed solid electrolyte prepared in Example 1 of the present invention and the PVDF-HFP polymer solid electrolyte; 3 (b) X-ray diffraction patterns of the mixed solid electrolytes prepared in Examples 1 to 3 of the present invention, wherein Example 1 is HSE-SO3-1, Example 2 is HSE-SO3-2, Example 3 is HSE-SO3-3, and Comparative Example 1 is HSE-SO3-0;
[0036] Figure 4 Test diagrams of the mixed solid electrolytes prepared in Examples 1 to 3 of the invention and Comparative Example 1 and Comparative Example 4, wherein (a to c) are fire test diagrams after burning for 10 minutes at room temperature, 160°C, and 200°C, respectively; (d) is a thermogravimetric test; (e) is an extreme fire test of the commercial Celgard2320 diaphragm of Comparative Example 4, (f) is an extreme fire test of Comparative Example 1; (g) is an extreme fire test of Example 3, wherein Example 1 is HSE-SO3-1, Example 2 is HSE-SO3-2, Example 3 is HSE-SO3-3, and Comparative Example 1 is HSE-SO3-0;
[0037] Figure 5 A schematic diagram of the structural assembly of a lithium oxygen battery assembled with a hybrid solid electrolyte prepared in Examples 1 to 3 of the present invention and Comparative Example 1;
[0038] Figure 6 Ion migration number test results of the hybrid solid electrolytes prepared in Examples 1 to 3 of the invention and Comparative Example 1, the inset figures are constant voltage polarization curves and EIS results before and after constant voltage polarization, (a) Comparative Example 1, (b) Example 1, (c) Example 2, (d) Example 3;
[0039] Figure 7 Conductivity test results of the mixed solid electrolytes prepared in Examples 1 to 3 of the invention and Comparative Example 1;
[0040] The diagrams are for illustrative purposes only. DETAILED DESCRIPTION
[0041] The PVDF-HFP, LATP, taurine, lithium hydroxide, N,N-dimethylformamide and acetone used in the embodiments of the present invention are all commercially available products, wherein the purity of PVDF-HFP is 99.9 wt.%.
[0042] Example 1
[0043] (1) Raw material drying treatment: PVDF-HFP and LATP were placed in a vacuum drying oven, set to 50°C and dried for 24 hours to remove moisture, and then placed in a glove box for standby use. The number average molecular weight of PVDF-HFP is 300,000; the particle size of LATP is 300 nm.
[0044] (2) Preparation of lithium taurine: 12.516 g of taurine and 2.395 g of lithium hydroxide were weighed and dissolved in deionized water, and then placed in a hydrothermal reactor, set at 80° C. for 12 hours to ensure complete reaction. The resulting clear solution was the lithium taurine solution. The water in the solution was removed using a freeze dryer at -40° C. to obtain a lithium taurine solid, and the blocky lithium taurine was crushed using an agate mortar.
[0045] (3) Lithium sulfonate doped polyvinylidene fluoride-hexafluoropropylene copolymer:
[0046] Magnesium oxide (MgO) catalyzed lithium taurine doping and modification of PVDF-HFP: 2.4 g PVDF-HFP, 0.076 g MgO, and 0.239 g lithium taurine were weighed and dissolved in an appropriate amount of N, N-dimethylformamide. After heating and stirring at 90 ° C for 5 h using a heating stirrer, the mixture was placed in a hydrothermal reactor and reacted at 90 ° C for 12 hours to obtain lithium sulfonate doped and modified polyvinylidene fluoride-hexafluoropropylene copolymer, named HSE-SO3-1;
[0047] (4) Preparation of polyvinylidene fluoride-hexafluoropropylene copolymer slurry modified by lithium aluminum titanium phosphate and lithium taurate:
[0048] Weigh 1.6g LATP, dissolve it in a mixed solution of N,N-dimethylformamide and acetone, and ultrasonicate for 3h to completely crush the blocky LATP to obtain a LATP solution; add HSE-SO3-1 to the LATP solution to obtain a slurry; stir the slurry at 500rpm for 48h, reduce the speed to 250rpm and stir for 24h to eliminate bubbles. During the stirring process, add acetone at any time and stir until the slurry is obviously attached to the wall when the cup is slightly shaken and still has a certain fluidity.
[0049] (5) Slurry coating and film formation
[0050] The stirred slurry was coated on a thin glass sheet using an infrared flat plate coating machine, where the coating height was 300 μm, and the glass sheet was placed in a vacuum drying oven at room temperature for 20 minutes, then heated to 60°C and dried for 10 hours to remove the solvent, to obtain a mixed solid electrolyte film; the film was gently removed with tweezers. It was cut into discs with a diameter of 16 mm and a thickness of 90 μm to 120 μm using a hydraulic slicer, and placed in a glove box with a water oxygen content of less than 0.1 ppm for standby use.
[0051] Optical photographs of the prepared hybrid solid electrolyte are shown in Figure 2. Figure 1 As shown, it can be seen that the surface is light yellow, which is mainly the color of PVDF-HFP treated with lithium taurine.
[0052] Example 2
[0053] The difference between Example 1 and Example 1 is that in step (1), the number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 400,000; and the particle size of the lithium aluminum titanium phosphate is 200 nm.
[0054] In step (3), magnesium oxide (MgO) catalyzes lithium taurine doping and modification of PVDF-HFP: 2.1 g PVDF-HFP, 0.067 g MgO, and 0.210 g lithium taurine are weighed and dissolved in an appropriate amount of N,N-dimethylformamide, heated and stirred at 90° C. for 5 h using a heating stirrer, and then placed in a hydrothermal reactor for reaction at 120° C. for 10 hours to obtain lithium sulfonate doped and modified polyvinylidene fluoride-hexafluoropropylene copolymer, named HSE-SO3-2;
[0055] In step (4), the polyvinylidene fluoride-hexafluoropropylene copolymer modified by lithium titanium aluminum phosphate and lithium taurine is deposited: 2.1g LATP is weighed and dissolved in a mixed solution of N, N-dimethylformamide and acetone, and ultrasonicated for 3 hours to completely crush the blocky LATP to obtain a LATP solution; HSE-SO3-2 is added to the LATP solution to obtain a slurry; the slurry is stirred at 500 rpm for 48 hours, and then the speed is reduced to 250 rpm and stirred for 24 hours to eliminate bubbles. During the stirring process, the dispersant is added at any time, and the slurry is stirred until the wall is obviously attached when the cup wall is slightly shaken and still has a certain fluidity.
[0056] The other steps are the same as those in the embodiment and will not be repeated here.
[0057] Example 3
[0058] The difference between Example 1 and Example 1 is that in step (1), the number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 200,000; and the particle size of the lithium aluminum titanium phosphate is 400 nm.
[0059] In step (3), magnesium oxide (MgO) catalyzes lithium taurine doping and modification of PVDF-HFP: 1.5 g PVDF-HFP, 0.048 g MgO, and 0.150 g lithium taurine are weighed and dissolved in an appropriate amount of N,N-dimethylformamide, heated and stirred at 90° C. for 5 h using a heating stirrer, and then placed in a hydrothermal reactor for reaction at 140° C. for 5 hours to obtain lithium sulfonate doped and modified polyvinylidene fluoride-hexafluoropropylene copolymer, named HSE-SO3-3;
[0060] In step (4), the polyvinylidene fluoride-hexafluoropropylene copolymer modified by lithium titanium aluminum phosphate and lithium taurine is deposited: 2.25g LATP is weighed and dissolved in a mixed solution of N, N-dimethylformamide and acetone, and ultrasonicated for 3 hours to completely crush the blocky LATP to obtain a LATP solution; HSE-SO3-3 is added to the LATP solution to obtain a slurry; the slurry is stirred at 500 rpm for 48 hours, and then the speed is reduced to 250 rpm and stirred for 24 hours to eliminate bubbles. During the stirring process, the dispersant is added at any time, and the slurry is stirred until the wall is obviously attached when the cup wall is slightly shaken and still has a certain fluidity.
[0061] The other steps are the same as those in the embodiment and will not be repeated here.
[0062] Example 4
[0063] The difference between Example 1 and Example 1 is that in step (1), the number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 500,000; and the particle size of the lithium aluminum titanium phosphate is 300 nm.
[0064] In step (3), magnesium oxide (MgO) catalyzes lithium taurine doping and modification of PVDF-HFP: 1.2 g PVDF-HFP, 0.038 g MgO, and 0.120 g lithium taurine are weighed and dissolved in an appropriate amount of N,N-dimethylformamide, heated and stirred at 90° C. for 5 h using a heating stirrer, and then placed in a hydrothermal reactor for reaction at 100° C. for 8 h to obtain lithium sulfonate doped and modified polyvinylidene fluoride-hexafluoropropylene copolymer, named HSE-SO3-4;
[0065] In step (4), the polyvinylidene fluoride-hexafluoropropylene copolymer modified by lithium titanium aluminum phosphate and lithium taurine is deposited: 2.8g LATP is weighed and dissolved in a mixed solution of N,N-dimethylformamide and acetone, and ultrasonicated for 3 hours to completely crush the blocky LATP to obtain a LATP solution; HSE-SO3-4 is added to the LATP solution to obtain a slurry; the slurry is stirred at 500 rpm for 48 hours, and then the speed is reduced to 250 rpm and stirred for 24 hours to eliminate bubbles. During the stirring process, acetone is added at any time, and the slurry is stirred until the wall of the cup is obviously attached when the cup is slightly shaken and still has a certain fluidity.
[0066] In step (5), HSE-SO3-4 still cannot form a film due to the excessive proportion of filler LATP and too little polymer, and the whole is in powder form. The reason may be that part of PVDF-HFP loses its polymer properties during the doping reaction.
[0067] The other steps are the same as those in the embodiment and will not be repeated here.
[0068] Comparative Example 1
[0069] The difference from Example 1 is that LATP is not added, and the preparation process is as follows:
[0070] (1) Raw material drying treatment: PVDF-HFP was placed in a vacuum drying oven, set to 50° C. and dried for 24 hours to remove moisture, and then placed in a glove box for standby use. The number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer was 300,000.
[0071] (2) Preparation of lithium taurine: 12.516 g of taurine and 2.395 g of lithium hydroxide were weighed and dissolved in deionized water, and then placed in a hydrothermal reactor, set at 80° C. for 12 hours to ensure complete reaction. The resulting clear solution was the lithium taurine solution. The water in the solution was removed using a freeze dryer at -40° C. to obtain a lithium taurine solid, and the blocky lithium taurine was crushed using an agate mortar.
[0072] (3) Lithium sulfonate doped polyvinylidene fluoride-hexafluoropropylene copolymer:
[0073] Magnesium oxide (MgO) catalyzed lithium taurine doping modification of PVDF-HFP: 2.4 g PVDF-HFP, 0.076 g MgO, 0.239 g lithium taurine were weighed and dissolved in an appropriate amount of N, N-dimethylformamide, heated and stirred at 90 ° C for 5 h using a heating stirrer, and then placed in a hydrothermal reactor at 90 ° C for 12 hours for doping reaction to obtain lithium sulfonate doped modified polyvinylidene fluoride-hexafluoropropylene copolymer, named HSE-SO3-0;
[0074] (4) Preparation of polyvinylidene fluoride-hexafluoropropylene copolymer slurry doped with lithium taurine:
[0075] Dissolve HSE-SO3-0 in a mixed solution of N,N-dimethylformamide and acetone to obtain a slurry; stir the slurry at 500 rpm for 48 hours, then reduce the speed to 250 rpm and stir for 24 hours to eliminate bubbles. During the stirring process, add dispersant at any time and stir until the slurry is obviously attached to the wall when the cup is slightly shaken and still has a certain fluidity.
[0076] (5) Slurry coating and film formation
[0077] The stirred slurry was coated on a thin glass sheet using an infrared flat plate coating machine, where the coating height was 300 μm, and the glass sheet was placed in a vacuum drying oven at room temperature for 20 minutes, then heated to 60°C and dried for 10 hours to remove the solvent, to obtain a mixed solid electrolyte film; the film was gently removed with tweezers. It was cut into discs with a diameter of 16 mm and a thickness of 90 μm to 120 μm using a hydraulic slicer, and placed in a glove box with a water oxygen content of less than 0.1 ppm for standby use.
[0078] Comparative Example 2
[0079] The difference from Example 1 is that MnO2 is used as a catalyst and the mass of MnO2 is 0.165g:
[0080] In step (3), the polyvinylidene fluoride-hexafluoropropylene copolymer modified by lithium sulfonate doping:
[0081] MnO2-catalyzed lithium taurine doped modified PVDF-HFP: Weigh 2.4g PVDF-HFP, 0.165g MnO2, and 0.239g lithium taurine and dissolve them in an appropriate amount of N,N-dimethylformamide. Use a heating stirrer to heat and stir at 90°C for 5h, then place it in a hydrothermal reactor at 90°C for 12 hours for doping reaction to obtain lithium sulfonate doped modified polyvinylidene fluoride-hexafluoropropylene copolymer.
[0082] The other steps are the same as those in the embodiment and will not be repeated here.
[0083] Comparative Example 3
[0084] Different from Example 1, PVDF-HFP is directly mixed with LATP, and the preparation process is as follows:
[0085] (1) Raw material drying treatment: PVDF-HFP and LATP were placed in a vacuum drying oven, set to 80°C and dried for 12 hours to remove moisture, and then placed in a glove box for standby use. Among them, the number average molecular weight of PVDF-HFP is 300,000; the particle size of LATP is 300 nm.
[0086] (2) Preparation of lithium aluminum titanium phosphate and polyvinylidene fluoride-hexafluoropropylene copolymer slurry:
[0087] Weigh 1.6g LATP, dissolve it in a mixed solution of N,N-dimethylformamide and acetone, and ultrasonicate for 3h to completely crush the blocky LATP to obtain a LATP solution; add 2.4g PVDF-HFP to the LATP solution to obtain a slurry; stir the slurry at 500rpm for 48h, then reduce the speed to 250rpm and stir for 24h to eliminate bubbles. During the stirring process, add acetone at any time and stir until the slurry is obviously attached to the wall when the cup is slightly shaken and still has a certain fluidity.
[0088] (3) Slurry coating and film formation
[0089] The stirred slurry was coated on a thin glass sheet using an infrared flat plate coating machine, where the coating height was 300 μm, and the glass sheet was placed in a vacuum drying oven at room temperature for 20 minutes, then heated to 60°C and dried for 10 hours to remove the solvent, to obtain a mixed solid electrolyte film; the film was gently removed with tweezers. It was cut into discs with a diameter of 16 mm and a thickness of 90 μm to 120 μm using a hydraulic slicer, and placed in a glove box with a water oxygen content of less than 0.1 ppm for standby use.
[0090] Comparative Example 4
[0091] Commercial Celgard 2320 membrane.
[0092] Comparative Example 5
[0093] Commercially available lithium aluminum titanate phosphate electrolyte.
[0094] Performance Testing:
[0095] Scanning electron microscopy: The hybrid solid electrolyte films prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were obtained by scanning electron microscopy at a scale of 1 μm. Figure 2 As shown, the surfaces of the mixed solid electrolytes of Examples 1 to 3 are uniformly loaded with LATP, the LATP interconnections provide angled contacts, and the internal phosphorus-oxygen tetrahedrons provide high lithium ion migration efficiency.
[0096] X-ray diffraction:
[0097] The X-ray diffraction results of the mixed solid electrolytes prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are as follows: Figure 3 As shown, the mixed solid electrolytes of Examples 1 to 3 have no impurity peaks as a whole, have high crystallinity, and have good suppression of the amorphous region.
[0098] Fire performance:
[0099] The fire performance of the mixed solid electrolytes of Examples 1 to 3 of the present invention and Comparative Examples 1 and 4 is as follows: Figure 4 As shown, it can be seen that Examples 1 to 3 are better than Example 4 in overall stability when burning with the outer flame of an alcohol lamp, and there is no ignition phenomenon. This is because the main body of Example 4 is polyethylene, and polypropylene organic matter is extremely flammable, which is not safe in extreme battery conditions. For Example 1, the polymer modified by lithium taurine contains a certain amount of inorganic salts, and the carbon chain structure of the polymer itself is ignited into carbon dioxide during the fire. The outer flame of the alcohol lamp does not reach the melting point of the inorganic salt, so the overall structure is maintained to a certain extent. For Example 3, the solid electrolyte with a high lithium titanium aluminum phosphate content was not ignited itself in a one-minute fire test, and the polymer responsible for bonding and coating the lithium titanium aluminum phosphate was modified with lithium taurine catalyzed by magnesium oxide, and the polymer itself had a partial crystal structure, which is consistent with the test results of the X-ray diffraction pattern. Therefore, Example 3 has the best extreme fire performance.
[0100] Battery assembly: A schematic diagram of the structural assembly of a hybrid solid electrolyte (HSE) applied to a lithium-oxygen battery is shown below: Figure 5 shown.
[0101] Lithium ion migration number test:
[0102] The test adopts the classic ion migration number test method to test the ion migration number of the hybrid solid electrolyte prepared in Examples 1 to 3 and Comparative Example 1. The test process is as follows:
[0103] 1. Assemble a lithium sheet-solid electrolyte-lithium sheet symmetrical battery, add 5 μL of electrolyte (1MLiTFSI+TEGDME) to ensure good contact, and place it in a glove box for 24 hours;
[0104] 2. Use an electrochemical workstation to perform EIS testing, the test conditions are 100000Hz-1Hz, and the scan rate is 5mV·s -1 , record the impedance data;
[0105] 3. Use an electrochemical workstation to perform constant voltage polarization on the above battery, with a perturbation voltage of 10mV and a perturbation time of 3600s, and stop after observing the current balance;
[0106] 4. Test EIS again with the same parameters as in step 2 and calculate the ion mobility using formula (1).
[0107]
[0108] Among them, I ss is the current after constant voltage polarization; I0 is the current before constant voltage polarization; ΔV is the polarization voltage; R ss is the impedance before constant voltage polarization; R0 is the impedance after constant voltage polarization.
[0109] The test results are as follows Figure 6 As shown, it can be seen that as the content of lithium aluminum titanium phosphate increases, the lithium ion migration number calculated by formula (1) also increases. This is because the phosphorus-oxygen tetrahedron inside the lithium aluminum titanium phosphate contacts and transmits lithium ions.
[0110] Conductivity test:
[0111] Assemble a steel sheet-solid electrolyte-steel sheet symmetrical battery, set the test frequency to 100000Hz-1Hz, the test rate to 5mV / s, and use an electrochemical workstation to test the bulk impedance (without fitting). Substitute the electrolyte thickness L, effective area S and the measured bulk impedance R into the ion conductivity calculation formula to calculate the lithium ion conductivity.
[0112]
[0113] Wherein, σ is the ionic conductivity; L is the thickness of the solid electrolyte; R is the solid electrolyte impedance; and S is the effective area of the solid electrolyte contacting the steel sheet.
[0114] The test results are as follows Figure 7As shown in the figure, it can be seen that as the content of lithium aluminum titanium phosphate increases, the lithium ion conductivity gradually increases. This is because the phosphorus and oxygen tetrahedrons inside the lithium aluminum titanium phosphate contact and transmit lithium ions.
[0115] The performance of the mixed solid electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3 is shown in Table 1 below.
[0116] Table 1 Performance of hybrid solid electrolyte
[0117]
[0118] As shown in Table 1, both the ion conductivity and the ion migration number are the lowest in Comparative Example 3. Theoretically, the performance of Comparative Example 3 filled with inorganic solid electrolyte should be better. However, in reality, due to the coating of polyvinylidene fluoride hexafluoropropylene with low ion conductivity, lithium ions cannot jump and transmit well between the phosphorus oxygen tetrahedrons of lithium titanium aluminum phosphate. Comparative Example 1 is a polymer electrolyte modified with lithium taurine catalyzed by magnesium oxide without adding lithium titanium aluminum phosphate. The ion conductivity and ion migration number are both considerable. After adding inorganic solid electrolytes to Examples 1 to 3, the high ion flux polymer coating connects the inorganic solid electrolyte lithium titanium aluminum phosphate to form a channel for lithium ion transmission efficiency. It can be seen that as the content of lithium titanium aluminum phosphate increases, the overall performance increases. This is because the internal structure has been converted from the polymer in Comparative Example 1 as the main body to the non-polar solid electrolyte as the main body.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A mixed solid electrolyte composition, characterized in that The invention is composed of polyvinylidene fluoride-hexafluoropropylene copolymer doped and modified by lithium titanium aluminum phosphate and lithium taurine, wherein the content of lithium titanium aluminum phosphate is 60%-70wt.%.
2. The mixed solid electrolyte composition according to claim 1, characterized in that The lithium taurine doped modified polyvinylidene fluoride-hexafluoropropylene copolymer is a product obtained by adding lithium taurine, a catalyst and polyvinylidene fluoride-hexafluoropropylene copolymer into a solvent, stirring and heating to 90-140° C., reacting for 5-20 hours and then cooling.
3. The mixed solid electrolyte composition according to claim 2, characterized in that The mass ratio of lithium taurate, catalyst and polyvinylidene fluoride-hexafluoropropylene copolymer is (1.2-2.4): (0.2-0.239): (0.038-0.076); the catalyst is MgO or MnO2; the solvent is DMF; Alternatively, the number average molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 200,000 to 500,000.
4. A hybrid solid electrolyte film, characterized in that: The mixed solid electrolyte composition according to any one of claims 1 to 3 is uniformly mixed with a dispersant, coated on a substrate, and dried to obtain the mixed solid electrolyte composition.
5. The hybrid solid electrolyte film according to claim 4, characterized in that: The dispersant is N,N-dimethylformamide and acetone, and the volume ratio of N,N-dimethylformamide to acetone is 1:(2-3); the thickness of the mixed solid electrolyte film is 100-130 μm.
6. A method for preparing a hybrid solid electrolyte film according to claim 4 or 5, characterized in that: The polyvinylidene fluoride-hexafluoropropylene copolymer doped with lithium titanium aluminum phosphate and lithium taurine and a dispersant are uniformly mixed, coated on a clean and smooth substrate, and vacuum dried to obtain the product; Or, the dispersant is N,N-dimethylformamide and acetone, and the volume ratio of N,N-dimethylformamide to acetone is 1:(2-3); Alternatively, the particle size of the lithium aluminum titanium phosphate is 200 to 400 nm.
7. The method for preparing a hybrid solid electrolyte film according to claim 6, characterized in that: The preparation method of lithium taurine is as follows: dissolving taurine and lithium hydroxide in deionized water at a molar ratio of (0.1-0.5):1; performing a hydrothermal reaction at 60-80° C. for 3-12 hours to obtain a reaction product; and freeze-drying at -30-40° C. to obtain lithium taurine.
8. The method for preparing a hybrid solid electrolyte according to claim 4, characterized in that: The method for modifying polyvinylidene fluoride-hexafluoropropylene copolymer by doping with lithium taurine is as follows: adding lithium taurine, a catalyst, and polyvinylidene fluoride-hexafluoropropylene copolymer to a solvent, stirring and heating to 90-140° C., reacting for 5-20 hours, and then cooling to obtain a product; Or, the mass ratio of lithium taurate, polyvinylidene fluoride-hexafluoropropylene and catalyst is (1.2-2.4): (0.2-0.239): (0.038-0.076); Alternatively, the catalyst is MgO or MnO2.
9. Use of the hybrid solid electrolyte film according to claim 4 or 5 in a lithium-air or lithium-oxygen battery.
10. A lithium-air or lithium-oxygen battery, characterized in that: It comprises an air positive electrode, a mixed solid electrolyte film as claimed in claim 4 or 5, and a metal lithium negative electrode; Preferably, the air positive electrode comprises a positive electrode current collector, carbon paper, a conductive material, a binder and a catalyst; Further preferably, the conductive material is conductive carbon black, carbon nanotubes, acetylene black, or ketjen carbon; More preferably, the binder is polyvinylidene fluoride or polytetrafluoroethylene.